Immunohistochemical analysis of homeobox protein expression in urothelial carcinoma of bladder - Md Akhir, Mohd Khairul Anuar (2016)
Urothelial carcinoma of the bladder is a common malignant neoplasm that has a poor prognosis and high grade. In order to prevent the tumour from recurring or becoming invasive, constant disease surveillance with periodic and long term cystoscopy examination is necessary. However, the monitoring and therapy regimen is expensive and causes a massive burden to patients and the government. Therefore, development of specific biomarkers for urothelial carcinoma for detection of early stage tumours as well as prediction of tumour recurrence becomes top priority. Homeobox genes are a family of genes that are involved in tumourigenesis. They might be potential prognostic markers for urothelial carcinoma of the bladder. The objectives of our study were to describe the expression of homeobox genes (NANOG, ISL1 and LHX5) and identify their cellular localisation in urothelial carcinoma. The correlation expressions between these three proteins were also carried out. Lastly, we correlated the expression of these genes with demographic factors and clinicopathological parameters. The expression of NANOG, ISL1 and LHX5 in 100 formalin-fixed paraffin-embedded urothelial carcinoma of the bladder tissues that were collected from Hospital Kuala Lumpur were determined by immunohistochemistry. Immunohistochemical staining results showed that the localization of NANOG, ISL1 and LHX5 antibodies were detected in the cytoplasm, nuclei and nuclear membrane of urothelial carcinoma of the urothelial cells. Positive expression of NANOG, ISL1 and LHX5 was detected in 100%, 94% and 98% of specimens respectively. The immunohistochemical expression of NANOG, ISL1 and LHX5 were not significantly associated with pathological stage (p= 0.127, 0.846 and 0.681 respectively) and grade (p=0.580, 0.588 and 0.099 respectively). There was also no significant correlation between NANOG expression with ISL1 and LHX5 expression. The immunohistochemical expression of NANOG, ISL1 and LHX5 were also not significantly associated with demographic factors such as gender (p=0.469, p=0.637 and p=0.910 respectively), race (p=0.718, p=0.858 and p=0.285 respectively) and age (p=0.067, p=0.803 and p=0.203 respectively) as well as with clinicopathological parameters such as lymph node metastasis (p=0.208, 0.621 and 0.586 respectively) and distant metastasis (p=0.240, p=0.170 and p=0.303 respectively). Interestingly, NANOG expression showed significant correlation with tumour invasion whereby the p-value is p=0.01. However, there was no significant association between tumour invasion and the expression of ISL1 and LHX5 in urothelial carcinoma of the bladder. In conclusion, NANOG and ISL1 are potential biomarkers for urothelial carcinoma of the bladder. NANOG is also a potential prognostic marker for urothelial carcinoma of the bladder invasion. Their role in urothelial carcinoma might be better understood with more functional studies that elucidate the phenotype-genotype correlations.